53 Acute procedural outcomes and CMR appearances of PVI using a point by point workflow – a comparison study. (October 2018) - O'Neill, L; Williams, S; Karim, R; Whitaker, J; Mukherjee, R; Harrison, J; Sim, I; Julia, J; Wright, M; O'Neill, M
Abstract : Background: The 'Close Protocol' workflow for pulmonary vein isolation (PVI) targeting pre-defined 'Ablation Index' (AI, a composite of contact force, time and power) values and minimising inter-lesion distance may optimise the creation of durable lesions. Cardiac MRI (CMR) is a useful tool to assess the appearances of post ablation scar. Aims: To compare procedural parameters, success rates and post ablation CMR scar burden in patients undergoing PVI using a point by point work flow to a cohort of historical controls. Methods: Procedural details and success rates were recorded in 29 patients undergoing 1st time PVI using a 'point by point' work flow by 2 operators. Comparison was made with a cohort of 20 consecutive historical controls undergoing PVI by the same operators using continuous drag lesions. CMR parameters pre- and post-ablation were recorded. To calculate total post ablation scar burden, scar maps were generated from atrial 3D late gadolinium enhancement (LGE) sequences using in-house software. Scar burden was calculated by thresholding the maps at 0.97 times the mean signal intensity of the blood pool using the image intensity ratio method. Scar width and ablation lesion gaps were assessed on 3D scar maps using custom made software. Results: Target AI values for Operator 1 were 400 anteriorly and 350 at the posterior wall and 400 throughout the LA for Operator 2. There were no significant differences in baseline demographics, duration of AF and CHADS2VASc score between the two groups. Procedural parameters and outcomes : Mean procedural time was significantly lower in the study group vs the control group (150.9±6.3 mins vs 186.1±10.12, p=0.004). The mean number of RF applications in the study group was significantly higher than in the control group (91.48±5.9 vs 21.2±2.3, p≤0.001). Complete PV isolation was achieved in all patients. There was no difference in the rates of first pass isolation or in the need for additional RF to achieve isolation between both groups. No complications occurred in either group. At a mean follow up of 6.8±0.9 months, 3 patients in the study group had a documented recurrence of AF. CMR analysis : Baseline pre-procedure LA area and end-diastolic volume (EDV) were similar in both groups (27.1±1.6 cm vs 28.3±1.1 cm, p=NS and 107.4±7.8 ml vs 114.9±4.8 ml, p=NS). Post-procedure CMR was carried out at a time interval of 3.7±1.1 months after ablation. Total post ablation scar burden was significantly lower in the study vs the control group (51.2%±1.9% vs 61.6±1.7%, p=0.001). Overall there was a greater reduction in LA area and EDV post procedure in the study vs the control group however this was not statistically significant. Analysis of ablation lesion gaps is ongoing. Conclusion: PVI using a 'point by point' workflow offers shorter procedural times and lower post ablation scar burden compared to a conventional approach. Further work is needed to determine if this protocol offers a long-term outcome benefit compared to a conventional approach.